EVALUASI KINERJA LALU LINTAS DAMPAK PEMBANGUNAN FLYOVER CIROYOM KOTA BANDUNG - Najla Chairunnisa; Sarrah Asmara; Dimas Zhafiruddin Syah; Lutfhi Ahmad Barwanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2025)
The increase in vehicle volume in Bandung City, particularly in the Ciroyom area adjacent to the railway and market area, has resulted in significant traffic congestion. This has prompted the construction of the Ciroyom flyover, which is expected to improve travel time efficiency and smooth vehicle traffic in the surrounding area. This study aims to evaluate travel time efficiency and analyze public perceptions of the Ciroyom flyover. This study uses a mixed-method approach, combining quantitative analysis of vehicle travel time before and after the flyover through descriptive statistics, with a qualitative approach through field surveys and questionnaires distributed to road users and residents. Performance evaluations were conducted on five variables: travel time efficiency, congestion, traffic smoothness, driving comfort, and driving safety. The results show that all variables obtained evaluation scores at the